UPAYA MENINGKATKAN KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL SIFAT OPERASI HITUNG BILANGAN BULAT DENGAN MENERAPKAN MODEL TGT DI KELAS V SD NEGERI 090 PANYABUNGAN - Sahriani Sahriani (Universitas Negeri Medan, 2017)
Abstract: Efforts to Improve Student's Ability in Completing the Problem of Operation Compute Integer By Applying the Model of TGT In Class V SD Negeri 090 Panyabungan. Subjects in this study amounted to 45 students. In Cycle I the average value of 66 tests with learning completeness of 53.33% and on Cycle II the average value of 80 tests with learning completeness up to 86.66%, and managed to give a complete learning outcomes in a classical. Teams Games Tournaments (TGT) learning models can improve students' understanding of the nature of the integer count operation, as evidenced by the observer's activity in Cycle I, among others, writing and reading 38%, working on LKS 32%, asking fellow friends 20%, asking teachers 5%, and that is not relevant to 5% teaching and learning activities. While the activity of students according to the observations in Cycle II, among others, write and read 32%, 40% work, ask fellow friends 18%, asked the teachers 6%, and that is not relevant to 4% teaching and learning activities. Keywords : Model TGT, Nature of Operation Compute Integer Abstrak : Upaya Meningkatkan Kemampuan Siswa Dalam Menyelesaikan Soal Sifat Operasi Hitung Bilangan Bulat Dengan Menerapkan Model TGT Di Kelas V SD Negeri 090 Panyabungan. Subjek dalam penelitian ini berjumlah 45 siswa. Pada Siklus I rata-rata nilai tes 66 dengan ketuntasan pembelajaran sebesar 53,33% dan pada Siklus II rata-rata nilai tes 80 dengan ketuntasan pembelajaran naik menjadi 86,66%, dan berhasil memberikan ketuntasan hasil belajar secara klasikal. Model pembelajaran Teams Games Tournaments (TGT) dapat meningkatkan pemahaman siswa tentang sifat operasi hitung bilangan bulat, terbukti dari aktivitas siswa menurut pengamatan pengamat pada Siklus I antara lain menulis dan membaca 38%, mengerjakan LKS 32%, bertanya sesama teman 20%, bertanya kepada guru 5%, dan yang tidak relevan dengan kegiatan belajar mengajar 5%. Sedangkan aktivitas siswa menurut pengamatan pada Siklus II antara lain menulis dan membaca 32%, bekerja 40%, bertanya sesama teman 18%, bertanya kepada guru 6%, dan yang tidak relevan dengan kegiatan belajar mengajar 4%. Kata Kunci : Model TGT, Sifat Operasi Hitung Bilangan Bulat